Keterbukaan dan Kepastian Hukum dalam Teori Kontrak Roscoe Pound - Martinelli, Imelda; Reinhart, Frederick; Natalie, Cicilia; Milianty, Yessa (Universitas Ekasakti, 2023)
The role of transparency and legal certainty in business contracts is crucial to prevent failures. This research, conducted through case study analysis and qualitative research methods, found that transparent business contracts, where the rights and obligations of the parties are clearly defined, significantly reduce the risk of misunderstandings and enhance trust among the involved parties. Meanwhile, legal certainty establishes a solid foundation, providing guidance for dispute resolution and reinforcing the integrity of business relationships. This study delves into the dynamics of transparency and legal certainty in the contract theory proposed by Roscoe Pound. Against the backdrop of rapid changes in the global business environment, questions about the extent to which Pound's concepts of legal certainty and transparency can be applied and integrated into modern business contract practices become paramount.The analysis indicates that while legal certainty is a key element in building a stable legal foundation, transparency is necessary to facilitate legal adaptation to social and economic changes, as grounded in Pound's research. The most significant findings of this study reflect the tension between the need for high legal certainty and the need for transparency to address the complexities of the modern market. In the context of Pound's theory, social justice through law is a crucial foundation in the design and implementation of business contracts. This study not only contributes to the understanding of Roscoe Pound's contract theory but also provides new insights into how these concepts can be applied in the dynamic legal and business framework of today. It is recommended that business practitioners collaborate with legal professionals and governments to establish clearer guidelines on transparency and legal certainty. In an increasingly complex business era, these steps are expected to assist business practitioners in building relationships based on integrity, trust, and long-term success.